The Prominent Role of National Judges in Interpreting the International Definition of Human Trafficking - Esser, Luuk B; Dettmeijer-Vermeulen, Corinne E (Anti-Trafficking Review, 2016)
Although there has been much discussion of the scope of the concept of human trafficking in international literature, the part played by national courts in interpreting definitions based on the international definition of human trafficking in the UN Trafficking Protocol has received little attention. When a judge interprets an offence, he or she clarifies or adds new meaning to it. The space for this is even greater when the underlying definition is broadly formulated, as in the case of the international definition of human trafficking. This article demonstrates that, although this international definition establishes the outer parameters within which conduct must be made a criminal offence, domestic courts still have room to flesh out the definition in national contexts. The role of national judges needs more consideration in today’s discourse on the legal definition of human trafficking.